SEJARAH PENCETAKAN AL-QUR`AN DI JAWA TENGAH - Ahmad Saifudin (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2021)
The purpose of this research is to find out the history of Qur’anic printing in Central Java. This is motivated by differences between previous researchers in terms of determining the company that printed the Qur`an first in Central Java. Some mentioned PT Thoha Putra Semarang and some others mentioned PT Menara Kudus. The difference of opinion arises because the data they use is not primary data. This research method uses historical research. Apart from PT Menara Kudus and PT Thoha Putra Semarang, this research data was also obtained from PT Tiga Serangkai Solo; as a form of continuation of the history of printing the Koran in Central Java. The data obtained and processed in this study are primary data, namely manuscripts printed by the three companies and interviews with directors or managers of these companies. The results of this research that PT Menara Kudus was the first company to print the Qur`an in Central Java, in 1959. Then it was followed by PT Thoha Putra Semarang in 1977. The development of printing the Qur`an continued until now, even more crowded with the presence of companies that were not involved in the world of printing the Qur`an, then participated in printing the Koran. This can be seen from the manuscripts printed by PT Tiga Serangkai Solo which look more contemporary. Keyword: History, Quranic printing